Alternately stacked thin film electrodes for high-performance compact energy storage. (December 2020) - Lin, Dou; Qian, Ou; Huo, Dexian; Pan, Qijun; Zhang, Shiping; Wang, Zhaoming; Han, Fangming; Wei, Bingqing
Abstract: High mass loading of active materials is crucial to improve the performance of electrochemical energy storage devices. However, high mass loading inevitably increases internal resistance, hinders electron conduction and ion diffusion, and ultimately leads to poor energy storage performance. Herein, a new type of supercapacitors with alternately stacked electrode configuration for high-performance compact energy storage is proposed, and fabricated by alternately stacking highly conductive MXene films as electrodes, and using a thin layer of gel electrolyte as an ionic carrier and a separator. The supercapacitor with 33-layer alternately stacked electrodes can achieve a high areal capacitance of 10.8 F cm −2 at the scan rate of 2 mV s −1, and reach a record volumetric energy density of about 10.4 mWh cm −3 in an aqueous gel electrolyte system, much higher than that of the supercapacitor with two-electrode configuration under the ultra-high loadings of the active materials. The novel design of the electrodes towards next-generation energy storage devices, not limited to supercapacitors, would offer distinctive opportunities for the energy storage systems with high mass loadings of active materials, to achieve high areal and volumetric energy densities. Graphical abstract: A newly-structured supercapacitor with alternately stacked MXene films as electrodes and gel electrolyte as a separator for compact energy storage is demonstrated. This structure can shorten the ion transport path, and increase the mass loadings of active materials without sacrificing performance. A high areal capacitance about 10.8 F cm −2 and a high volumetric energy density up to 10.4 mWh cm −3 have been achieved. Image 1 Highlights: A new-structured supercapacitor with alternately stacked MXene film electrodes is firstly introduced. Alternately stacked configuration of the supercapacitor increases the mass loading of active materialwithout sacrificing power performance. Alternately stacked configuration results in an enhanced volumetric energy density and an ultra-high areal capacitance. Alternately stacked configuration offers insight into the improvement of energy storage performance at the device scale.